'I know I should, but I haven't': advance care directive decision-making by baby boomers in South Australia. Issue 1 (1st June 2011) - Bradley, S
Abstract : Aim: To describe the results of a grounded theory study on what influences advance directive decision-making by Baby Boomers in South Australia As longevity increases and chronic illness becomes the leading cause of death, the demands boomers will make on healthcare is of paramount importance to governments around the world. The literature speculates about these demands, yet there is little evidence to guide policy makers, academics and others interested in advance care planning. By understanding boomer use of advance directives, evidence can be provided of healthcare lifestyles important to this generation. Thus, a grounded theory study of seven South Australians aged 43–61 years was undertaken to identify the factors that influenced these boomers' advance directive decision-making. In analysis of the data, elements of their decision-making reflected critical areas of concern similar to those cited by persons already engaged in advance directive or advance care planning through terminal illness or frail age. The difference for participants in this study was that they were still 'young', in good health and had experienced the healthcare environment through relationships with others. These experiences presented a process of contemplation for developing a long-term plan for future healthcare needs. Contemplation was found to be a significant element of the decision-making process for the participants, which evolved as additional social and psychological influences impacted on them – ultimately leading them to create, reject or further contemplate their own advance directives.